HAK NON MUSLIM TERHADAP HARTA WARIS (Hukum Waris Islam, KHI dan CLD-KHI di Indonesia) - Syafi’ie, M. (Al-Mawarid Jurnal Hukum Islam, 2010)
This paper discusses the pros and cons of the inheritance rights of non Muslims in the treasury of Islamic thought., Differences of opinion concerning the inheritance rights of non Muslims are preceded by a difference of opinion about terminology or infidels and apostates. Differences of opinion Ulama of classical and contemporary Islamic thinker in this matter was influenced instrumentation Islamic family law in Indonesia. Fiqh opinions as expressed by the scholars classic especially Imam Shafii become the foundation of family law in Islamic Law Compilation (KHI) as the Presidential Instruction No. 1 of 1991. According to the rules of KHI Article 171 (b, c), religious differences between muwarris and heir of a barrier right to inheritance. While the opinion of contemporary Islamic thinkers such as Abdullah Ahmed An Naim and Asgar Ali Engineer, an inspiration ijtihad discussion CLD-KHI. In chapter 2 CLD-KHI mentioned that the problem of different religions is not a barrier because of the legacy inherited. CLD-KHI drafting team believes, religious discrimination in inheritance rights is part of a form of discrimination, injustice and violation of human rights and should be replaced with a more contextual. Keywords: hak, waris, non muslim, keadilan, dan HAM